(untitled) (Journal of the Management Sciences, 2026)
This study examined the application of queuing model in Chukwuemeka Odumegwu Ojukwu University Teaching Hospital with the aim of assessing patient flow, service efficiency, and waiting time management within the hospital system. The study was motivated by the persistent challenge of long patient waiting time and congestion experienced in the hospital due to the increasing demand for healthcare services and limited-service facilities. The research adopted the M/M/1 single-server queueing model to analyze the service process using field data collected over three days. Findings revealed an average inter-arrival time of 6 minutes and an average service time of 4 minutes, resulting in an arrival rate of 0.17 patients per minute and a service rate of 0.25 patients per minute. The utilization factor was found to be 68%, indicating heavy use of available service resources, while the probability of system idleness was 32%. The average queue length was approximately 1.445 patients, the average waiting time in the queue was 8.5 minutes, and the average waiting time in the system was 12.5 minutes, showing moderate congestion and service delay. The study concluded that although the hospital demonstrates reasonable operational performance, improvements are required to reduce waiting time and enhance patient satisfaction. It recommended effective resource management, strategic capacity planning, improved patient communication, adoption of queue management technologies, continuous monitoring of performance indicators, and enhancement of customer care services to improve efficiency and ensure better healthcare service delivery.